The Dramatic Sound of the Digital World: A Review on Duyulan Tiyatro: Radyo Oyunu Yazım Tekniği - Gonca Ekin (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
Müşerref Öztürk Çetindoğan’s book Duyulan Tiyatro: Radyo Oyunu Yazım Tekniği discusses radio theater from a historical perspective, with a special emphasis on the space of sound and the aesthetic possibilities of the auditory, and examines its technical and theoretical features by evaluating the opportunities oﬀered by developing technology. The book serves as a guide for those who want to write radio plays. At the same time, it ﬁlls an important gap in our theater literature by including conceptual and theoretical discussions about radio theater.